Amelioration of drought stress in wheat by combined application of PGPR, compost, and mineral fertilizer. (28th May 2017) - Kanwal, Shadana; Ilyas, Noshin; Batool, Nazima; Arshad, Muhammad
ABSTRACT: Among various abiotic stresses, global drought reduces global growth and yield of wheat. Present research has been designed to ameliorate the adverse effects of drought stress on wheat by combined application of plant growth-promoting rhizobacteria (PGPR), compost, and mineral fertilizers. In this experiment, the role of fertilizer, compost, and PGPR inoculation to ameliorate drought stress was studied in two wheat varieties at vegetative stage. Water stress adversely affects morphology, physiology, and biochemistry of the wheat plant. Inoculated seed with compost and mineral fertilizer grown in drought condition showed 43% increase in relative water content (RWC) of 9.39% in Membrane Stability Index and 82.20% in chlorophyll as compared to control. Drought affected the accumulation of osmolytes, but PGPR in combination with compost and mineral fertilizer under drought stress triggered higher accumulation of soluble sugar and proline content, i.e., 28.96% and 73.91%, respectively. It is concluded from this research that PGPR in combination with compost and mineral fertilizer considerably reduces the effect of drought on wheat by enhancing the physiological (RWC, membrane stability, chlorophyll content, and water potential) and biochemical (proline and sugar) aspects of the plant.